Desain Struktur Atas Gedung Rawat Inap 3 Lantai RSUD Nganjuk Menggunakan Standart Nasional Indonesia (SNI) - Ines Indria Wati; Edy Gardjito; Sigit Winarto; Muhammad Heri Nastotok; Imam Mustofa (Faculty of Engineering, Kadiri University, 2021)
The hospital building is one of the building facilities that is developed continuously. The building was built as an effort to fulfill health facilities. In its construction, the hospital building must be properly planned so that it is safe to use. Planning includes the design and calculation of structural details. Several hospitals in the Nganjuk area added building units to meet the needs of the community, one of which was the Nganjuk Hospital which added a building to support services. Planning a multi-storey building is a solution because it will be able to accommodate many patients. This plan aims to plan the structure of the Nganjuk Regional General Hospital Building. The planning carried out includes the calculation of structural dimensions, calculation of loading, and calculation of reinforcement which were analyzed using SAP2000 software. The calculation results show that the dimensions of the columns used are 40/40 and 15/15 for practical columns, the dimensions of the beams are 35/50 and 30/40 and 25/35. Reinforcement on beams obtained diameters of 16 and 10 mm, reinforcement on columns obtained diameters of 19 and 10 mm, while on plates obtained diameters of 10 mm. Thus, these results can be used as a reference in the implementation of the construction of the Nganjuk Regional General Hospital Building.